2016
DOI: 10.1016/j.ctcp.2015.05.002
|View full text |Cite
|
Sign up to set email alerts
|

A pilot randomised controlled trial (RCT) investigating the effectiveness of reflexology for managing pregnancy low back and/or pelvic pain

Abstract: Many pregnant women with low back and/or pelvic pain (LBPP) use pain medications to manage this pain, much of which is self-prescribed and potentially harmful. Therefore, there is a need to find effective nonpharmacological treatments for the condition. Reflexology has previously been shown to help nonspecific low back pain. Therefore; a pilot RCT was conducted investigating reflexology in the management of pregnancy-LBPP. 90 primiparous women were randomised to either usual care, a reflexology or footbath int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 28 publications
0
29
0
1
Order By: Relevance
“…All reflexology treatments were carried out by one experienced maternity reflexologist and lasted for approximately 30 minutes. Details of the treatment routine have been reported elsewhere [33].…”
Section: Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…All reflexology treatments were carried out by one experienced maternity reflexologist and lasted for approximately 30 minutes. Details of the treatment routine have been reported elsewhere [33].…”
Section: Interventionsmentioning
confidence: 99%
“…In order to evaluate any changes related to reflexology treatments during pregnancy a group of low risk pregnant women who were experiencing pain as a result of LBPGP were recruited. This investigation was part of a large pilot study reported elsewhere [33] to evaluate strategies aimed at preventing or managing LBPGP during pregnancy as few guidelines are available, and with physiotherapy being the primary intervention in most cases. Literature reviews have highlighted that CAM may be helpful for managing this type of pain [30,34].…”
Section: Introductionmentioning
confidence: 99%
“…HVLA thrust techniques) oraz techniki kompresji komory czwartej mózgu mogą powodować zagrożenie dla ciężarnej i płodu bądź prowadzić do przedwczesnego porodu. W związku z tym, nie badano efektywności tych procedur w terapii LPP [39]. Doniesiono również o pozytywnym wpływie postępowania chiropraktycznego na odczuwany ból i niesprawność.…”
Section: Alternative Methodsunclassified
“…Therefore, the effectiveness of these procedures in LPP treatment has not been studied [39]. There have been reports on positive effects of chiropractic treatment on pain and disability.…”
Section: Alternative Methodsmentioning
confidence: 99%
“…At this point, women who expressed an interest in participation were provided with a participant information sheet. The process of assessing eligibility and randomisation is described elsewhere [9]. Inclusion and exclusion criteria for The CAM in Pregnancy Trial are detailed in Table 1.…”
Section: Methodsmentioning
confidence: 99%